The [B3(NN)3]+ and [B3(CO)3]+ Complexes Featuring the Smallest π‐Aromatic Species B3+. Issue 6 (6th January 2016) - Jin, Jiaye; Wang, Guanjun; Zhou, Mingfei; Andrada, Diego M.; Hermann, Markus; Frenking, Gernot
Abstract: We report the spectroscopic identification of the [B3 (NN)3 ] + and [B3 (CO)3 ] + complexes, which feature the smallest π‐aromatic system B3 + . A quantum chemical bonding analysis shows that the adducts are mainly stabilized by L→[B3 L2 ] + σ‐donation. Abstract : Minimal π systems : The [B3 (NN)3 ] + and [B3 (CO)3 ] + complexes are identified through infrared photodissociation spectroscopy. The complexes feature the smallest π‐aromatic system B3 + . Quantum chemical bonding analysis reveals that the adducts are stabilized by L→[B3 L2 ] + σ‐donation.